Comparative Analysis of the Metabolites and Biological Activity of Cultivated and Wild Lignosus rhinocerotis. (17th September 2022) - Wu, Bingmin; Wang, Yange; Zeng, Lishan; Li, Wengkun; An, Lin; Li, Jingyan; Zhan, Ruoting; Kang, Huasheng; Liu, Li; Lin, Ying; Zhang, Guifang
Abstract : In this paper, Lignosus rhinocerotis (Cooke) Ryvarden ( L. rhinocerotis ) cultivated in rice medium (LRR) and in sawdust medium (LRS) was harvested. Then, in terms of the LRR, LRS, and wild L. rhinocerotis (LRW), the total flavonoid contents, total polyphenol contents, total polysaccharide contents, and metabolites were detected; antioxidants of their aqueous extracts and anti-inflammatory of their polysaccharides were performed. In addition, the possible mechanism of the polysaccharides of L. rhinocerotis inhibiting lung damage was elucidated. The results showed that 32 compounds were characterized in L. rhinocerotis, including flavonoids, terpenoids, lignans, and steroids and there were 20 compounds in cultivated and wild L. rhinocerotis ; LRR has the highest total polyphenol and flavonoid contents, as well as ABTS and DPPH scavenging capacity. The total polysaccharide contents and the FRAP scavenging capacity of wild L. rhinocerotis were higher than those of cultivated L. rhinocerotis . The inhibition of polysaccharides of LRW (PLRW) on LPS-induced MRC-5 damage was stronger than that of the polysaccharides from cultivated L. rhinocerotis . The PLRW may alleviate lung damage by inhibiting the NLRP3 pathway and thereby suppressing the inflammatory response. In summary, both cultivated and wild L. rhinocerotis are abundant in bioactive components and have antioxidant and anti-inflammatory activities.